Working with statistics : an introduction to quantitative methods for social scientists - Reid, Stuart (Cambridge : Polity Press, 1987)
An argument for statistics. Methodological considerations. The vocabulary of social research. Odering the data. Summarizing the data. Taking a sample. Working with two variables. Working with three or more variables.
Keywords: Statistics; Social sciences; Authors, Irish -- Homes and haunts -- Ireland; Statistics; Social sciences -- Statistical methods